Easy and Fast Production of Solketal from Glycerol Acetalization via Heteropolyacids - Diana Julião; Fatima Mirante; Salete S. Balula (Molecules, 2022)
This work presents an effective and fast procedure to valorize the main waste produced from the biodiesel industry, i.e., the glycerol. The acetalization of glycerol with acetone represents an effective strategy to produce the valuable solketal, a fuel additive component. In this work, the catalytic efficiency of different commercial heteropolyacids (HPAas) was compared under a solvent-free system. The HPAs used were H3[PW12O40] (PW12), H3[PMo12O40] (PMo12) and H4[SiW12O40] (SiW12). The influence of reactional parameters such as reactants stoichiometry, catalyst concentration and reaction temperature were investigated in order to optimize experimental conditions to increase cost-efficiency and sustainability. HPAs demonstrated to be highly efficient for this type of reaction, presenting a high and fast glycerol conversion, with high selectivity to solketal under sustainable conditions (solvent-free system and room temperature medium). The activity of HPAs using 3% to glycerol weight and a glycerol/acetone ratio of 1:15 followed the order: PW12 (99.2%) > PMo12 (91.4%) > SiW12 (90.7%) as a result of the strong acidic sites after 5 min. In fact, only 5 min of reaction were needed to achieve 97% of solketal product in the presence of the PW12 as a catalyst. This last system presents an effective, selective and sustainable catalytic system to valorize glycerol.